The Royal Pardon and Criminal Procedure in Early Modern England - Beattie, J. (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1987)
AbstractThe study of the royal power of pardon illuminates the English criminal justice system, particularly in the eighteenth century. Pardons granted on condition of transportation acted as a counterbalance to the harshness of the “Bloody Code”, notably after 1689 when a considerable increase in the number of capital statutes threatened a vast rise in executions. The documents generated by the pardon process, especially petitions and judges' reports, suggest the boundaries within which the royal authority was exercised and the relative weight given to the nature of the offence, the character of the accused and the influence of the social and political elite. A study of those who were pardoned and those on the other hand who were hanged reveals that the overriding aim of those who administered the criminal law was to interpret and enforce the law so as to enhance its terror while underlining the king's justice and humanity. The royal power of pardon was an essential element in that administration of the law. During the late-eighteenth and early-nineteenth centuries, the convictions and attitudes which supported the criminal justice system came under scrutiny, and the cruelty and capriciousness of capital punishment was the subject of particular criticism. The reform of the law in the early decades of the nineteenth century sharply curtailed the role that the royal pardon had played in the administration of justice for several centuries.